Relaksasi Autogenik Untuk Menurunkan Tekanan Darah dan Tingkat Kecemasan Penderita Hipertensi Esensial di Panti Sosial Tresna Wredha Abiyoso Pakem Yogyakarta - Umi Istianah; Sri Hendarsih; Sugeng Sugeng (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
Essential hypertension is 95% of existing hypertension cases. Hypertension has been a deadly disease that many people in the developed and developing countries call the silent killer because the disease does not have the typical symptoms that are realized by the sufferer. The anticipation for this disease is by implementing a positive lifestyle and habits. To overcome hypertension, it can be done with medications or alternative treatment (non-pharmacological therapies) for example acupressure, herbal medicine, massage therapy, breathing and relaxation, treatment on the mind and body; biofeedback, meditation, hypnosis, etc. This study aims to determine the effect of autogenic relaxation towards the decrease of blood pressure and anxiety levels of patients with essential hypertension at PSTW Abiyoso Pakem Yogyakarta. This study is a quasi-experimental design with Non-Equivalent Control Group with pre and post-test. The study was conducted at PSTW Abiyoso Pakem and PSTW Budhi Luhur Kasongan Bantul with a sample of 30 people in the intervention group and 30 people in the control group. The sample was obtained with purposive sampling. The sample criteria were the elderly with essential hypertension, aged at least 50 years, experiencing at least mild anxiety, having no hearing loss, able to communicate well and are willing to become respondents. Measurements of blood pressure and anxiety levels were performed before giving autogenic relaxation techniques, the intervention group was given the standard therapy plus autogenic relaxation and the control group was only given standard therapy. The data for each group were analyzed by Wilcoxon test and compared by Mann Whitney test. Most respondents were female, 70% in the intervention group and 80% in the control group. Age of respondents in the intervention group on average was 72.4 years old, the youngest was 56 years old and the oldest was 85 years old. The control group on average was 71.6 years, the youngest was 50 and the oldest was 86 years old. Results of statistical test in the intervention group for systolic BP before and after relaxation using Wilcoxon test obtained significance 0.001 (p <0.05), and 0005 for the control group. Diastolic blood pressure tests for the intervention group and the control group were respectively 0.001 and 0.012. From the results of the Mann-Whitney test between the intervention group and the control group, it was obtained p = 0520 for systolic blood pressure, p = 0411 for diastolic and p = 0.000 for anxiety levels. It can be concluded that autogenic relaxation has an effect on lowering blood pressure and anxiety levels in patients with essential hypertension at PSTW Abiyoso Yogyakarta.